CONSTITUTIONAL CHALLENGES TO SCHOOL RULES* - Marita Carnelley (Obiter, 2022)
The following four court applications set the stage for the debate on challenges to school disciplinary rules during the past two years: In July 2005, the mother of Sunali Pillay brought an application in the Equality Court against the principal and governing body of Durban Girls’ High School. The application aimed to restrain the school from taking disciplinary action against her daughter based on the girl’s refusal to remove a nose stud which was regarded by the school as a violation of the school’s code of conduct. The grounds for the application were that their refusal violated her constitutional rights to equality and freedom of religion, conscience, belief and culture. In September 2005, the Western Cape Residents’ Association brought an application in the Cape High Court on behalf of the parents of Bernel Williams. The application was to ensure her attendance at the matric farewell function hosted by Parow High School. It was argued that the school’s refusal to allow her to attend the function, based on her continued unacceptable behaviour, infringed her constitutional right to equality, dignity and freedom of expression. Similarly, the Supreme Court of Canada had to determine, on 2 March 2006, whether the refusal by the school authorities to allow an orthodox Sikh student, Gurbaj Singh, to wear a kirpan (religious object resembling a dagger) to the school he was attending, was an infringement of his freedom of religion under section 2(a) of the Canadian Charter of Rights and Freedoms. On 22 March 2006, the House of Lords in England decided in favour of the decision by the head-teacher and governors of Denbigh High School to exclude Shabina Begun from the school unless she conformed to the school dress code. Begun insisted on wearing a hijab (long coat-like garment) and not the shalwar kameeze she had been wearing for the previous two years and which, according to the evidence, satisfied the Islamic clothing requirements. She argued that her exclusion infringed inter alia on her right to manifest her religion under art 9 of the European Convention on Human Rights. In all these matters the constitutional rights of the learner were weighed up against the right of the school to ensure a disciplined environment through the strict observance of the school rules. Although only two of the four applications were successful, it is encouraging that parents and learners are prepared to test decisions taken by schools – an indication that a human rights culture is taking root at secondary school level on both a national and international level. The aim of this note is to discuss these judgments within the parameters of the rights of learners vis-à-vis the rights of other learners and the necessity for discipline and a safe schooling environment. The first section of the note is devoted to an examination of each of these judgments. Thereafter, the issues are discussed with specific reference to the South African constitutional principles and the application of the Promotion of Equality and Prevention of Unfair Discrimination Act 4 of 2000.